2016
DOI: 10.1155/2016/7463130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Continuous Venovenous Hemofiltration on E-Selectin, Hemodynamic Stability, and Ventilatory Function in Patients with Septic-Shock-Induced Acute Respiratory Distress Syndrome

Abstract: Objective. To investigate the effects of 72-hour early-initiated continuous venovenous hemofiltration (ECVVH) treatment in patients with septic-shock-induced acute respiratory distress syndrome (ARDS) (not acute kidney injury, AKI) with regard to serum E-selectin and measurements of lung function and hemodynamic stability. Methods. This prospective nonblinded single institutional randomized study involved 51 patients who were randomly assigned to receive or not receive ECVVH, an ECVVH group (n = 24) and a non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Previous study indicated that continuous hemofiltration application can significantly lower the 28-day mortality (38% vs. 71%, P = 0.011) and in-hospital mortality (62% vs. 86%, P = 0.04) in patients with severe burns and acute kidney injury [ 19 ]. However, the 72-h early-initiated continuous hemofiltration treatment has no effect on the 28-day mortality in patients with septic-shock-induced acute respiratory distress syndrome (ARDS) without acute kidney injury [ 20 ]. Our previous study indicated that continuous hemofiltration improved the inflammatory biomarkers but no advantage in mortality in patients with secondary hemophagocytic syndrome [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study indicated that continuous hemofiltration application can significantly lower the 28-day mortality (38% vs. 71%, P = 0.011) and in-hospital mortality (62% vs. 86%, P = 0.04) in patients with severe burns and acute kidney injury [ 19 ]. However, the 72-h early-initiated continuous hemofiltration treatment has no effect on the 28-day mortality in patients with septic-shock-induced acute respiratory distress syndrome (ARDS) without acute kidney injury [ 20 ]. Our previous study indicated that continuous hemofiltration improved the inflammatory biomarkers but no advantage in mortality in patients with secondary hemophagocytic syndrome [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Duration of treatment varied from 1 to 96 h spread over 1–7 days. Fourteen studies used CVVH [19, 37, 47, 50, 51, 53, 56, 57, 60, 63, 66-69], 17 used endotoxin adsorption [7, 9, 34, 38, 42-46, 48, 52, 55, 58, 59, 64, 65, 70], 3 used nonspecific adsorption [39, 40, 68], 2 used cytokine removal [54, 62], 2 used CPFA [41, 61], 2 used combined CVVH and adsorption [49, 68], and 1 used plasma exchange [36].…”
Section: Resultsmentioning
confidence: 99%
“…Vasopressor requirement was described either as norepinephrine dose [19, 34, 39, 40, 51, 57, 61, 62, 70], SOFA cardiovascular system score [48, 52], dopamine dose [65], or a vasopressor index [38]. A change in vasopressor use was reported in 3 studies using CVVH [19, 51, 57], 6 studies using endotoxin removal devices [34, 38, 48, 52, 65, 70], 2 studies using nonspecific adsorption [39, 40], 1 study using CytoSorb [62], and 1 study using CPFA [61].…”
Section: Resultsmentioning
confidence: 99%
“…Sepsis and acute respiratory distress syndrome (ARDS) are two types of syndromes needing intensive care with multiple characteristics. Both are common and highly lethal and have significant negative effects on survivors [20]. Sepsis-induced ARDS has an estimated incidence of over 40% and is the leading cause of ARDS death [21].…”
Section: Discussionmentioning
confidence: 99%
“…As a complex pathological process, ARDS is regulated by transcription factors as well as miRNA. A miRNA is a small endogenous non-coding RNA molecule that includes approximately [18][19][20][21][22][23][24] nucleotides. It usually complements sites in the 3' untranslated region of the target messenger RNA for inhibiting the expression of post-transcriptional gene [8].…”
Section: Introductionmentioning
confidence: 99%